Aplikasi Pemantau Pertumbuhan Meningkatkan Pemantauan Mandiri Ibu terhadap Stunting - Rokhaidah; Herlina (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Children are the future of the nation who have the right to grow and develop properly. The problem of growthchildren in Indonesia is still quite high. The prevalence of stunting in 2017 was 29.6%, far above the minimumlimit set by WHO, which is 20%. One of the pillars of preventing stunting is warning and evaluation. Growthmonitoring can be done using an application accessed via a smartphone which is designed to facilitate a varietyof health problems. The purpose of this study was to analyze the effect of training on the use of child growthapplications on the independent practice of mothers in controlling stunting. This study used a quasi-experimentaldesign with a pre and post test control group design. The sample of this research is mothers who have childrenunder five at Posyandu Arjuna, Baros Village, perhaps 60 people with purposive sampling technique. Theinstrument used was a practice observation sheet in child growth, the results of statistical tests with ManWhitney analysis showed a p value of 0.007, which means that it shows the difference between the independentpractice of the control group and the intervention group at the time of the final test so that it can show that theuse of growth monitoring applications has a good effect on practice. independent mother in a condition ofstunting. Researchers suggest analyzing the factors that can influence mother's motivation to increase childgrowth.